Agrarian Capitalism and Poor Relief in England, 1500-1860 - Patriquin, Larry. author. aut Link
IX, 254 p.
Keywords: This book examines the evolution of public assistance for the poor in England from the late medieval era to the Industrial Revolution. Placing poor relief in the context of the unique class relations of agrarian capitalism, it considers how and why relief in England in the early modern period was distinct.